Ditch Terrace Effect Of Erosion Land Farming In Horticulture In The Village Rurukan Tomohon City. - Tilda Titah; Yani Ezrah B. Kamagi; Djoni Kaunang; Meldi Tieneke M. Sinolungan (Sam Ratulangi University, 2023)
The purpose of this study was to determine the amount of erosion that occurs on sloping land with mound terraces planted with carrots. The research was carried out in the field by making three research plots with a size of 11 m x 4 m, consisting of 1). Traditional bund plots have 11 bunds, 2). The terrace plots of mounds without plastic mulch have 8 mounds and 3). The terrace plots of mounds with plastic mulch have 8 mounds. Erosion measurement results are calculated using the formula: Total weight of eroded soil = (X gram / Y ml) x volume of water in a bucket. Where: X = Weight of oven-dry soil; Y = Total sediment samples (650 ml). The data obtained is then arranged in the form of tables and graphs and then described descriptively. The results showed that the most erosion was in plot 2 of 606.3077 gr/plot with a rain intensity of 17.31 mm/hour and the least amount of erosion was in plot 1 of 0.0692 gr/plot with a rain intensity of 5.86 mm/hour. Keywords: Terraced bunds, Erosion Abstrak Tujuan penelitian ini adalah untuk mengetahui besarnya erosi yang terjadi pada lahan miring dengan teras guludan yang ditanami wortel. Penelitian dilakukan di lapangan dengan membuat petak penelitian dengan ukuran 11 m x 4 m sebanyak tiga petak, yang terdiri atas : 1). Petak guludan tradisionil, mempunyai 11 guludan, 2). Petak teras guludan tanpa mulsa plastik, mempunyai 8 guludan dan 3). Petak teras guludan dengan mulsa plastik mempunyai 8 guludan. Data hasil pengukuran erosi, dihitung dengan rumus : Berat total tanah tererosi = (X gram / Y ml) x volume air ember. Di mana : X = Berat tanah kering oven; Y = Jumlah sedimen cuplikan (650 ml). Data-data yang diperoleh selanjutnya disusun dalam bentuk tabel dan grafik kemudian diuraikan secara deskriptif. Hasil penelitian diperoleh bahwa erosi terbanyak pada petak 2 sejumlah 606,3077 gr/petak dengan intensitas hujan sebesar 17,31 mm/jam dan jumlah erosi tersedikit pada petak 1 sejumlah 0,0692 gr/petak dengan intensitas hujan 5,86 mm/jam. Kata kunci : Teras guludan, Erosi